Distance learning principles for effective design, delivery, and evaluation - Mehrotra, Chandra; Hollister, C. David; McGahey, Lawrence (Thousand Oaks, California London SAGE, 2001)
In reaction to the growth of distance learning, this book lays out practical principles and advice to help teachers and administrators design, implement and evaluate distance learning courses using a variety of formats.
Keywords: Distance education -- Curricula; Education, Higher -- Curricula; Instructional systems -- Design